2012
DOI: 10.7727/wimj.2011.040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gongronema latifolium Ethanol Leaf Extract on Gastric Acid Secretion and Cytoprotection in Streptozotocin-induced Diabetic Rats

Abstract: Objectives: Gongronema latifolium leaves have been used in folklore medicine to manage diabetes mellitus and alleviate dyspepsia. This study aimed to provide a pharmacological basis to the medicinal use of Gongronema latifolium as an antidiabetic and antiulcerogenic agent in diabetes mellitus. Methods: Ethanol extract from the leaf (200 mg/kg bodyweight) of Gongronema latifolium was administered to both streptozotocin-induced diabetic and control groups orally for 14 days. Gastric acid secretion was measured a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 41 publications
3
18
0
Order By: Relevance
“…The hypoglycaemic potential of the V. amygdalina and G. latifolium was observed to be more pronounced in rats that received the extracts after induction of diabetes mellitus by streptozotocin. This observation is in agreement with the reports of Uchenna et al [31]and Owu et al [32] who reported that the leaves of the plants possess anti-diabetic potential in that it reduces blood glucose levels in streptozotocin-induced diabetic rats.…”
Section: Discussionsupporting
confidence: 93%
“…The hypoglycaemic potential of the V. amygdalina and G. latifolium was observed to be more pronounced in rats that received the extracts after induction of diabetes mellitus by streptozotocin. This observation is in agreement with the reports of Uchenna et al [31]and Owu et al [32] who reported that the leaves of the plants possess anti-diabetic potential in that it reduces blood glucose levels in streptozotocin-induced diabetic rats.…”
Section: Discussionsupporting
confidence: 93%
“…Several reports on antimicrobial screening studies on G. latifolium and/or with other plant leaves is well documented (Eleyinmi, 2007;Bankole et al, 2012;Ikegbunam et al, 2014;Morebise, 2015;Anyanwu and Okoye, 2017) because of the desire to provide cost effective and safe antimicrobial agents. However, the use of G. latifolium leaves in folklore medicine by different ethnic groups for treatment of diseases such as malaria, nausea, anorexia, diabetes, hypertension, constipation, dysentery, etc., had earlier been reported (Morebise et al, 2006;Nwinyi et al, 2008;Owu et al, 2012;Okpala, 2015;Usoh et al, 2016). Gongronema latifolium leaves are also eaten fresh, with pourage or roasted yam and/or plantain, spiced in soups, as gravy, etc., for its nutritional and medicinal benefits (Owu et al, 2012).…”
Section: Introductionmentioning
confidence: 60%
“…However, the use of G. latifolium leaves in folklore medicine by different ethnic groups for treatment of diseases such as malaria, nausea, anorexia, diabetes, hypertension, constipation, dysentery, etc., had earlier been reported (Morebise et al, 2006;Nwinyi et al, 2008;Owu et al, 2012;Okpala, 2015;Usoh et al, 2016). Gongronema latifolium leaves are also eaten fresh, with pourage or roasted yam and/or plantain, spiced in soups, as gravy, etc., for its nutritional and medicinal benefits (Owu et al, 2012). The need to broaden raw material base and search for novel sources of antimicrobials is a global challenge preoccupying research institutes, nutraceutical, pharmaceutical industries and academia.…”
Section: Introductionmentioning
confidence: 60%
“…Origin and Distribution G. latifolium is of West African Origin (Nelson, 1965). It is found throughout Nigeria and other tropical countries such as Guinea-Bissau, Western Cameroon and Sierra Leone (Owu et al, 2012). It is an edible rainforest plant indigenous to South Eastern part of Nigeria.…”
Section: The Plant: Gongronema Latifoliummentioning
confidence: 99%